Pendampingan Sekolah Siaga Bencana Sebagai Upaya Mitigasi Bencana di SMK Kehutanan Qomarul Huda Lombok Barat - Lily Maysari Angraini; Syamsuddin Syamsuddin; Rahadi Wirawan; Nurul Qomariyah; Bakti Sukrisna (Universitas Mataram, 2019)
Based on its geographical location, West Nusa Tenggara Province is located in a disaster-prone area. Because generally disaster hazards can occur anywhere with little or no warning, it is very important to be prepared for disaster hazards to reduce the risk of their impacts. One of the most strategic efforts is through learning or training to improve the ability of the community to respond to disasters by creating a Disaster Preparedness School. The purpose of this activity is to realize the implementation of disaster management activities in schools / madrasas. The method used is (a) direct instruction to improve partner understanding related to disaster and disaster mitigation materials, (b) Group Discussion Forum to develop disaster learning modules and (c) simulations to improve disaster response partner skills. This activity will be held in the Qomarul Huda Narmada Forest High School in West Lombok-NTB. The output target of this activity is the formation of an evacuation route map as well as an explanation and the establishment of a disaster learning module that can be used in the learning process. It is hoped that by developing disaster preparedness school programs will contribute effectively to early prevention of disaster hazards.Keywords: Disaster Preparedness School, disaster mitigation, earthquake.